Amidinothiourea‐linked covalent organic framework for the adsorption of heavy metal ions. Issue 1 (10th August 2021) - Wang, Heping; Feng, Bang; Zhang, Qianwen; Du, Qiang; Bai, Qiuhong; Li, Cong; Shen, Yehua
Abstract: For the first time, a novel amidinothiourea‐linked covalent organic framework (COF) (TpAt) has been successfully synthesized by the condensation between 1, 3, 5‐triformylphloroglucinol and amidinothiourea via vacuum solvothermal reaction, and was further utilized for the adsorption of metal ions from aqueous solution. The effects of initial concentration, pH and contact time on the adsorption process were investigated. As a result, the TpAt COF showed maximum binding capacities as high as 95.44, 100.76 and 99.08 mg g –1 for Cr(III), Cd(II) and Cu(II) within 180 min at the initial concentration of 100 mg L –1, respectively. The isotherms of metal ions onto TpAt could be described by the Freundlich isotherm equation, and the adsorption kinetics followed the pseudo‐second‐order model. The TpAt could be reused for more than five adsorption–elution cycles, whilst basically maintaining its original adsorption performance and the structural integrity of the COF layers. The robust adsorption efficiency can be attributed to the coordination between metal ions and N, O and S atoms in the TpAt framework. The TpAt COF represents an ideal candidate for the removal of heavy metal ions in environmental pollution treatment. © 2021 Society of Industrial Chemistry. Abstract : A novel amidinothiourea‐linked covalent organic framework was synthesized and used to adsorb Cr, Cd and Cu from aqueous samples.